Contesting Syariah Laws in Malaysia: Religion, human rights and the state's response - Mohamad, Marzuki (Canadian Center of Science and Education, 2017)
Malaysia is a multiracial country with Islam as the Religion of the Federation. Its Federal Constitution is crafted in a way that Islam - the religion of the Malay majority - occupies special position in the constitution and makes significant presence in public life. But Malaysia is not a full-fledged Islamic state. Secular criminal and civil laws are in force and attempts to introduce Islamic criminal laws (hudūd) were thwarted by the provisions in the constitution itself. While the more conservative Muslim groups view the entrenched position of Islam in the constitution as one of the most important pillars of Malaysian nation, the more liberal groups see it as a hindrance to the creation of a more liberal and progressive Malaysia. This paper aims at analyzing the contestations between the two groups on the implementation of syariah laws and the impacts of these contestations on politics and law in contemporary Malaysia.